AN ANALYSIS OF STUDENTS WRITING ABILITY IN USING TRANSITION SIGNAL IN DESCRIPTIVE PARAGRAPH AT EIGHTH GRADE OF SMP ISLAM TERPADU DHU’AFA MERANGIN ACADEMIC YEAR 2021/2022 - Murnianti S.Pd M.Hum; Elmaida S.Pd.I M.Pd; Eki Kurniawan S.Pd.I M.Pd (INOVISH JOURNAL, 2022)
The students still difficult in using transition signal especially in writing descriptive paragraph. The researchers have conducted a research to analyze the students’ ability in writing a paragraph at SMP Islam Terpadu Dhu’afa Merangin. This research has focused on the students’ writing ability in using transition signal in descriptive paragraph. The type of this research is descriptive quantitative at the eighth grade of SMP Islam Terpadu Dhu’afa Merangin academic year 2021/2022. The students were consisting of 21 students. For representative sample, the researcher used total sampling. The technique in collecting data was used test. Then analyzing the data from the mean score of the students’ writing ability in using transition signal of descriptive paragraph. Based on he result of the test, it shown that the mean score of students was 70.24 (incomplete). It can be concluded that some students still confused in writing descriptive paragraph by using transition signal. Key words: Writing ability, Transition Signal, Descriptive Paragraph